Studying the experience of the state regulation of innovative projects in Almaty (Вестник КазНУ. Серия Экономическая, 2016)
Today Kazakhstan applies all existing tools in the world to supportinnovation. This article analyzes the current state of state regulation of innovativeactivity in Almaty. In this connection it revealed that innovationplay a big role; innovative activity in the country is not a source of increasingthe degree of competitiveness in the world market. Providing statesupport of innovative business growth potential of the innovation spherein Almaty is very high, taking into account the competitive advantages ofthe city in the national economic system – the large number of qualifiedpersonnel, a developed infrastructure, implemented by government supportmeasures, favorable location and investment climate. Apply belowmentionedbenefits important for our country, as, according to our survey,it is the problem of tax brakes factor in taking the initiative in this regard.